Emerging drugs for partial-onset epilepsy: a review of brivaracetam - Gao L; Li SC (Dove Medical Press, 2016)
Lan Gao,1 Shuchuen Li2 1Deakin Population Health SRC, Faculty of Health, Deakin University, Burwood, Victoria, 2School of Biomedical Sciences and Pharmacy, The University of Newcastle, Callaghan, NSW, Australia Abstract: There are more than 12 new antiepileptic drugs approved in the last 2 decades. Even with these newer agents, seizure remission is still unachievable in around 30% of patients with partial-onset seizures (POS). Brivaracetam (BRV) is chemically related to levetiracetam (LEV) and possesses a strong binding affinity for the synaptic vesicle protein 2A tenfold above that of LEV, and other possible modes of antiepileptic actions. BRV is now under Phase III development for POS, but data from one Phase III trial also suggested its potential efficacy for primary generalized seizures. The purpose of this review is to provide updated information on the mechanisms of action of the available antiepileptic drugs, with a focus on BRV to assess its pharmacology, pharmacokinetics, clinical efficacy, safety, and tolerability in patients with uncontrolled POS. To date, six Phase IIb and III clinical trials have been performed to investigate the efficacy, safety, and tolerability of BRV as an adjunctive treatment for patients with POS. Generally, BRV was well tolerated and did not show significant difference in safety profile, compared to placebo. The efficacy outcomes of BRV, although not consistent across trials, did indicate that BRV was a promising add-on therapy for patients with POS. In conclusion, the many favorable attributes of BRV, like its high oral efficacy, good tolerability, dosing regimen, and minimal drug interaction, make it a promising antiepileptic therapy for patients with uncontrolled partial-onset epilepsy. Keywords: brivaracetam, partial-onset epilepsy, drug-resistant epilepsy, randomized controlled trial, review